Long-Term Pulmonary Damage From SARS-CoV-2 in an Infant With Brief Unexplained Resolved Events: A Case Report - Nosetti, Luana; Agosti, Massimo; Franchini, Massimo; Milan, Valentina; Piacentini, Giorgio; Zaffanello, Marco (Frontiers in Medicine, 2021)
A brief unexplained resolved event (BRUE) is an event observed in a child under one year of age in which the observer witnesses a sudden, brief but resolved episode of change in skin color, lack of breathing, weakness or poor responsiveness. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of coronavirus disease-2019 (COVID-19). We report the case of a previously healthy, full-term infant infected with SARS-CoV-2. When he was 8 months old, his grandfather and great-uncle both died of severe pneumonia and his mother developed respiratory symptoms and fever. Over the following months he was seen five times in the emergency room and was hospitalized twice for recurrent BRUE. On the first hospital admission, after the second emergency room visit, he twice tested positive at nasopharyngeal swab tests for COVID-19. On the second hospital admission, after the fifth emergency room visit, chest computed tomography revealed typical SARS-CoV-2 pneumonia. At follow-up examination 6 months later, mild respiratory distress required administration of inhaled oxygen (0.5 L/min) and chest computed tomography disclosed a slight improvement in pulmonary involvement The clinical manifestation of pulmonary complications from COVID-19 infection was unusual. This is the first report of an infant at high-risk for BRUE, which was the only manifestation of long-term lung involvement due to SARS-CoV-2 pneumonia.